ACCELERATING AGRICULTURAL RECOVERY AFTER THE SIBOLGA FLASH FLOOD: A SYSTEMATIC LITERATURE REVIEW FOR DESIGNING A HOUSEHOLD FOOD SECURITY PROGRAM - Christin Imelda Girsang; Handayani Saragih; Rosmadelina Purba; Meriaty Tarigan; Difan Halim (CAKRAWALA: Journal of Citizenship Teaching and Learning, 2026)
This study examines the acceleration of agricultural recovery following the Sibolga flash flood, which severely affected household food systems. It aims to synthesize scientific evidence on effective food-security-based agricultural recovery strategies using a Systematic Literature Review (SLR) approach. The research data were drawn from relevant scientific literature published within the past five years on agricultural recovery, household food security, and flash floods. The findings indicate that successful recovery is determined by a combination of technical, social, and institutional interventions that strengthen farmers’ resilience capacities. In conclusion, accelerating agricultural recovery requires an integrative, community-based strategy that combines socioecological dimensions with public policy to build resilient and sustainable household food systems in disaster-prone areas.